2020
DOI: 10.1073/pnas.2006620117
|View full text |Cite|
|
Sign up to set email alerts
|

Rocks in the auxin stream: Wound-induced auxin accumulation and ERF115 expression synergistically drive stem cell regeneration

Abstract: Plants are known for their outstanding capacity to recover from various wounds and injuries. However, it remains largely unknown how plants sense diverse forms of injury and canalize existing developmental processes into the execution of a correct regenerative response. Auxin, a cardinal plant hormone with morphogen-like properties, has been previously implicated in the recovery from diverse types of wounding and organ loss. Here, through a combination of cellular imaging and in silico modeling, we demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(119 citation statements)
references
References 56 publications
2
117
0
Order By: Relevance
“…Auxin accumulates within a day at the wound site and directly activates expression of the WUSCHEL related homeobox 11 ( WOX11 ) transcription factor, which works redundantly with WOX12 to enable the transition of the local cambium cells to root founder cells within 4 days following the cut ( Liu et al, 2014 ; Hu and Xu, 2016 ). Accumulating evidence from recent publications on root regeneration emphasizes the importance of auxin during the replenishment of a single cell, a cluster of damaged root cells, or even regeneration of a complete de novo root tip ( Canher et al, 2020 ; Hoermayer et al, 2020 ; Matosevich et al, 2020 ). Depending on the severity and type of damage, the mode of action that allows for sufficient auxin accumulation in order to facilitate the regeneration process varies.…”
Section: Wound-induced Hormone Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Auxin accumulates within a day at the wound site and directly activates expression of the WUSCHEL related homeobox 11 ( WOX11 ) transcription factor, which works redundantly with WOX12 to enable the transition of the local cambium cells to root founder cells within 4 days following the cut ( Liu et al, 2014 ; Hu and Xu, 2016 ). Accumulating evidence from recent publications on root regeneration emphasizes the importance of auxin during the replenishment of a single cell, a cluster of damaged root cells, or even regeneration of a complete de novo root tip ( Canher et al, 2020 ; Hoermayer et al, 2020 ; Matosevich et al, 2020 ). Depending on the severity and type of damage, the mode of action that allows for sufficient auxin accumulation in order to facilitate the regeneration process varies.…”
Section: Wound-induced Hormone Signalingmentioning
confidence: 99%
“…Upon death of a group of vascular stem cells, for example, by bleomycin-induced DNA damage, the natural auxin flow is disrupted through downregulation of auxin transporters, resulting in an auxin redistribution, much alike rocks in a stream. However, similar to single cell death, no auxin biosynthesis could be observed during the recovery from vascular stem cell death ( Canher et al, 2020 ). However, following full root tip excision, YUCCA9-dependent auxin biosynthesis was found to be indispensable to allow regeneration of a de novo tip ( Matosevich et al, 2020 ).…”
Section: Wound-induced Hormone Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The chromate-treated med18 mutant displays a root twinning phenotype, which is associated with altered auxin response and distribution in roots (Ruiz-Aguilar et al, 2020). Furthermore, a recent study revealed that the injured provascular cells obstruct auxin flow and that this leads to auxin accumulation in endodermal cells, which triggers an auxin-dependent cell replenishment and tissue regeneration program (Canher et al, 2020). These observations suggest that auxin orchestrates post-embryonic root growth through the balance between cell death and regeneration.…”
Section: Introductionmentioning
confidence: 96%
“…The regulatory interactions between the different cell types of the root SCN are complex and nonintuitive and computational tools are essential to understanding systemic behavior. Developmental processes such as auxin flow within the root and lateral shoot branching have been mathematically modeled to better understand and predict system-level behavior (Canher et al, 2020;Prusinkiewicz et al, 2009). Some models implement different scales of the system to simulate, understand, and predict system-level behavior as a whole.…”
Section: Introductionmentioning
confidence: 99%